Effect of Soil Types on The Development of Matric Suction and Volumetric Water Content for Dike Embankment During Overtopping Tests - Hassan, Marwan Adil; Mohamad Ismail, Mohd Ashraf (Civil Engineering Journal, 2018)
The resistance of dike materials has a great effect on the development of hydraulic engineering around the world. It helps to understand the mechanism of dike failure occurred due to the influence of hydraulics and Geotechnical parameters. The overtopping moment is one of the main failures that reduces the stability of the dike embankment through initiating the breach channel inside dike crest as a result of water flow above the downstream slope of the dike. Two spatial overtopping tests were conducted at in Hydraulic Geotechnical laboratories at the University Sains of Malaysia to observe the evolution of matric suction and volumetric water content for two soil types of sand and very silty sand soils. A pilot channel was cut in dike crest along the side wall of the small flume channel to represent the transition water flow from upstream into downstream slopes during overtopping test. The results indicated that the matric suction decreases due to the increase of volumetric water content during the saturation of dike body. The proportion increasing and decreasing of volumetric water content and matric suction is lower in very silty sand than those in sand soil due to the presence of fine particles in previous soil.